Entomological indicators of malaria transmission prior to a cluster-randomized controlled trial of a ‘lethal house lure’ intervention in central Côte d’Ivoire - Rosine Z. Wolie; Alphonsine A. Koffi; Leslie Ayuk-Taylor; Ludovic P. Ahoua Alou; Eleanore D. Sternberg; Oulo N’Nan-Alla; Yao N’Guessan; Amal Dahounto; Welbeck A. Oumbouke; Innocent Z. Tia; Simon-Pierre A. N’Guetta; Jackie Cook; et al. (Malaria Journal, 2022)
Abstract Background A study was conducted prior to implementing a cluster-randomized controlled trial (CRT) of a lethal house lure strategy in central Côte d’Ivoire to provide baseline information on malaria indicators in 40 villages across five health districts. Methods Human landing catches (HLC) were performed between November and December 2016, capturing mosquitoes indoors and outdoors between 18.00 and 08.00 h. Mosquitoes were processed for entomological indicators of malaria transmission (human biting, parity, sporozoite, and entomological inoculation rates (EIR)). Species composition and allelic frequencies of kdr-w and ace-1 R mutations were also investigated within the Anopheles gambiae complex. Results Overall, 15,632 mosquitoes were captured. Anopheles gambiae sensu lato (s.l.) and Anopheles funestus were the two malaria vectors found during the survey period, with predominance for An. gambiae (66.2%) compared to An. funestus (10.3%). The mean biting rate for An. gambiae was almost five times higher than that for An. funestus (19.8 bites per person per night for An. gambiae vs 4.3 bites per person per night for An. funestus) and this was evident indoors and outdoors. Anopheles funestus was more competent to transmit malaria parasites in the study area, despite relatively lower number tested for sporozoite index (4.14% (63/1521) for An. gambiae vs 8.01% (59/736) for An. funestus; χ2 = 12.216; P < 0.0001). There were no significant differences between the proportions infected outdoors and indoors for An. gambiae (4.03 vs 4.13%; χ2 = 0.011; P = 0.9197) and for An. funestus (7.89 vs 8.16%; χ2 = 2.58e−29; P = 1). The majority of both infected vectors with malaria parasites harboured Plasmodium falciparum (93.65% for An. gambiae and 98. 31% for An. funestus). Overall, the EIR range for both species in the different districts appeared to be high (0.35–2.20 infected bites per human per night) with the highest value observed in the district of North-Eastern-Bouaké. There were no significant differences between transmission occurring outdoor and indoor for both species. Of the An. gambiae s.l. analysed, only An. gambiae sensu stricto (14.1%) and Anopheles coluzzii (85.9%) were found. The allelic frequencies of kdr and ace-1 R were higher in An. gambiae (0.97 for kdr and 0.19 for ace-1 R ) than in An. coluzzii (0.86 for kdr and 0.10 for ace-1 R ) (P < 0.001). Conclusion Despite universal coverage with long-lasting insecticidal nets (LLINs) in the area, there was an abundance of the malaria vectors (An. gambiae and An. funestus) in the study area in central Côte d’Ivoire. Consistent with high insecticide resistance intensity previously detected in these districts, the current study detected high kdr frequency (> 85%), coupled with high malaria transmission pattern, which could guide the use of Eave tubes in the study areas.